GRDAN’S UPRISING IN THE PLANS AND ARCHIVES OF THE APOSTOLIC SEE - KATARINA MITROVIĆ; MARIJA KOPRIVICA (Истраживања, 2024)
This study of the uprising of the voivode Grdan (1596–1597) was conducted within a wider context of the Apostolic See and Pope Clement VIII’s plans for missionary work by Franciscan Observants and Jesuits in the regions ruled by the Ottomans that was intended to strength Catholic congregations. In the years preceding the Long War (1593–1606), a belief emerged that the Ottoman Empire had weakened enough to easily collapse in the face of an attack by united Christian states backed by major uprisings among the Christians under their rule. The Apostolic See believed this would pave the way for mass conversion of Orthodox Christians and Muslims. Such beliefs were promoted by various adventurists and self-proclaimed servants of several royal courts. This paper is primarily based on the correspondence of Clement VIII and Cardinal Cinzio Aldobrandini with Patriarch Jovan II Kantul and Archbishop Toma Ursini, as well as on statements by Lazzaro Soranzo in his work L’Ottomanno. The paper will also pinpoint more precisely voivode Grdan’s uprising in comparison to what historiography has told us. Also, the names of some leaders of the people that supported him will be identified.